A protein crystallisation screening kit designed using polyethylene glycol as major precipitant1. Issue 29 (7th August 2015) - Liu, Yue; Zhang, Xian-Fang; Zhang, Chen-Yan; Guo, Yun-Zhu; Xie, Si-Xiao; Zhou, Ren-Bin; Cheng, Qing-Di; Yan, Er-Kai; Liu, Ya-Li; Lu, Xiao-Li; Lu, Qin-Qin; Lu, Hui-Meng; et al.
<x xml:space="preserve">Abstract</x> A protein crystallisation screening kit was designed through a step-by-step procedure. It showed significantly improved performance in crystallisation screening.